1999
DOI: 10.1183/09031936.99.13108799
|View full text |Cite
|
Sign up to set email alerts
|

Systemic effects of inhaled corticosteroids on growth and bone turnover in childhood asthma: a comparison of fluticasone with beclomethasone

Abstract: Inhaled steroids are frequently used in childhood asthma, but concerns based on limited objective evidence remain, regarding long-term side-effects. In this study the systemic effects of standard doses of inhaled steroids in childhood asthma were assessed, comparing beclomethasone dipropionate (BDP) with fluticasone propionate (FP). The study was prospective, randomized and double-blind. Twenty-three steroid-naive children with moderately severe asthma, aged 5-10 yrs, were allocated either BDP (400 microg x da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
64
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 37 publications
2
64
0
1
Order By: Relevance
“…60 Several studies [60][61][62][63] have looked at younger children to minimize the confounder of puberty. Three studies [60][61][62] found no deleterious effects of standard doses of beclomethasone or fluticasone on BMD in children 12 years and younger. However, a study 63 daily) for a mean (SD) of 2.9 (1.6) years revealed that lumbar BMD was more than 1 SD below the mean in 35% of treated patients compared with controls (P = .001).…”
Section: Primary Recommendationsmentioning
confidence: 99%
“…60 Several studies [60][61][62][63] have looked at younger children to minimize the confounder of puberty. Three studies [60][61][62] found no deleterious effects of standard doses of beclomethasone or fluticasone on BMD in children 12 years and younger. However, a study 63 daily) for a mean (SD) of 2.9 (1.6) years revealed that lumbar BMD was more than 1 SD below the mean in 35% of treated patients compared with controls (P = .001).…”
Section: Primary Recommendationsmentioning
confidence: 99%
“…All patients in Rao and colleagues' study 202 completed the initial 10 weeks and were well matched (except for immunoglobulin E levels, which were significantly higher in the BDP group).…”
mentioning
confidence: 99%
“…Only Gustafsson and colleagues 201 reported a power calculation (the outcome used was PEF) and neither of the trials stated that they used an ITT analysis. In the study by Rao and colleagues, 202 the three arms ran for 10 weeks. After this period, the placebo arm merged with the FP arm as it was considered unethical to continue the placebo for longer, thus breaking randomisation.…”
mentioning
confidence: 99%
See 2 more Smart Citations